Maize hybrids with high yield potential for lowlands, mid-altitudes, and highlands. - CGIAR Research Program on Maize (2019)
The best elite hybrids were selected from the project. The following objective is to validate their yield and agronomic characteristics through their evaluation in a greater number of localities. The best ones will be released to Mexican seed companies.